An ultraviolet sulfur dioxide detection using an open-path optical fiber based sensor for enclosed building monitoring application - Zul Rasyied, Ab. Rasat (2021)
This thesis describes the detection of Sulfur Dioxide (SO2) in the UV region. Increasing urban areas make the energy demand highly increased, thus more such as fossil fuel plant, environment, automotive and chemical-based industries need to be operated and constructed. Most of the commercially available SO2 sensors are chemical absorption-based which is a chemical component that will react with SO2 and change the electrical parameter properties such as its conductance, resistance or capacitance. Hence, the concentration of gas will be measured by the changes in electrical properties. This type of sensor has several weaknesses such as high input power, lower resolution, higher temperature and humidity dependence, difficult to achieve sensitivity, selectivity, and specificity in the presence of mixture gases. Therefore, the development of a new SO2 based fiber optic sensor is to decide the optimum wavelength for the SO2 to work on the next step. The system of sensors mentioned in this dissertation is a fiber-based open path device. It is dependent on the spectral of absorption of light by the SO2 gas. The absorption takes roles in the gas absorption cell made from stainless steel in a cylinder shape. The sensor system architecture requires durable material and can survive the most rigorous weather conditions. A deuterium-halogen bulb is used as the light source where it can provide UV light with a wavelength starting from 190nm to 2000nm. The spectrometer is used as a detector to detect the light source spectral interfaced with analysis software. Then the optimum absorption is analysed to get the best wavelength for assumption within the region of 200 nm to 235 nm by using 50 cm cell length as the optimum cell length. It is found that the highest peak of absorption cross section is 1.81248E-18 cm2/molecules centered at a wavelength of 215.65 nm. The findings of CO2 and O2 cross-sensitivity experiments for SO2 indicate that measurements in this field have no effect. The concentration measurement result has validate there is 3.38 ppm less than the original concentration of SO2 in the tank provided by the manufacturer. As this experiment has been done in the confined space in the lab, it is already similar to enclosed building application. Future work for this sensor will look at installing and testing the sensor into the enclosed room of food preservation or enclosed space of sulfuric acid manufacture industry and by using real-time monitoring with LabVIEW software. Further tests will look at a wider variety of gas mixtures and testing other gases within the UV range.